Fiber Lasers III: Technology, Systems, and Applications 2006
DOI: 10.1117/12.660942
|View full text |Cite
|
Sign up to set email alerts
|

Non-silica microstructured optical fibers for mid-IR supercontinuum generation from 2 μm - 5 μm

Abstract: We have performed numerical simulations to investigate the optimization of compound glass microstructured optical fibers for mid IR supercontinuum generation beyond the low loss transmission window of silica, using pump wavelengths in the range 1.55-2.25 µm. Large mode area fibers for high powers, and small core fiber designs for low powers, are proposed for a variety of glasses. Modeling results showed that for Bismuth and lead oxide glasses, which have nonlinearities ~10 x that of silica, matching the disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…However, we note that 0-6 THz is an important frequency range because the frequency width [full-width at half-maximum (FWHM)] for a 200-fs transform-limited Gaussian pulse is 2.2 THz, and it is, therefore, this part of the Raman spectrum that provides the long wavelength gain for soliton self-frequency shifting (SSFS). In our previous study of multicomponent glass MOFs, we showed the spectra from simulations performed for Bi glass WW fiber for the same seed pulse parameters and with: 1) SPM term only; 2) SPM and self-steepening terms; and 3) including the Raman response [10]. The overall shape of the continuum was similar in all cases, and we concluded that the initial continuum generation is not highly dependent on the Raman response in the fiber.…”
Section: A Numerical Modelmentioning
confidence: 88%
See 2 more Smart Citations
“…However, we note that 0-6 THz is an important frequency range because the frequency width [full-width at half-maximum (FWHM)] for a 200-fs transform-limited Gaussian pulse is 2.2 THz, and it is, therefore, this part of the Raman spectrum that provides the long wavelength gain for soliton self-frequency shifting (SSFS). In our previous study of multicomponent glass MOFs, we showed the spectra from simulations performed for Bi glass WW fiber for the same seed pulse parameters and with: 1) SPM term only; 2) SPM and self-steepening terms; and 3) including the Raman response [10]. The overall shape of the continuum was similar in all cases, and we concluded that the initial continuum generation is not highly dependent on the Raman response in the fiber.…”
Section: A Numerical Modelmentioning
confidence: 88%
“…1(b). In the small-core Bi MOF simulations, we fixed the pulse energy at 1 nJ, T 0 = 0.2 ps (FWHM), and fiber length to be equal to 40 mm, as this combination was found to be suitable for demonstrating supercontinuum in our earlier study [10]. As described in Section IV-C, for the large-mode fiber simulations, the seed pulse energy was increased to 30 nJ.…”
Section: B Simulations Demonstrating the Significance Of Dispersion mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the wide gain bandwidth of Tm-doped and Tm-Ho co-doped laser systems, sub-100 fs pulse trains at 2 mm can be efficiently generated using all-solid-state diode-pumped technology. Short mode-locked pulse trains in this spectral region are of major interest in time-resolved molecular spectroscopy, IR supercontinuum REVIEW www.advmat.de generation, [57] and frequency metrology. Moreover, high-energy ultrashort pulses at $2 mm find specific applications in highorder harmonic and high-efficiency soft-X-ray generation [58] and for optical relativistic effects.…”
Section: Nanotubes As Saturable Absorbersmentioning
confidence: 99%
“…Recently a number of works devoted to soft glass based PCFs are reported 3,[5][6][7][8][9][10] . The nonlinear refractive index of some of these glasses is up to few hundred times higher than in the case of standard silica glass and its transmission window goes up to 15μm 6 .…”
Section: Introductionmentioning
confidence: 99%